mRNA vaccines: A novel weapon to control infectious diseases - Tian, Yuying; Deng, Zhuoya; Yang, Penghui (Frontiers in Microbiology, 2022)
Infectious diseases have always threatened human life, but with the development of vaccines, effective strategies for preventing and controlling these diseases has become available. The global outbreak of COVID-19 ushered in the advent of mRNA vaccine technologies, which quickly led to the introduction of mRNA vaccines effective against SARS-CoV-2. The success of this approach has stimulated research into the use of mRNA vaccines in the fight against other emerging as well as remerging infectious diseases. This review examines the constructive strategies and delivery systems used in mRNA vaccines and provides an overview of current clinical trials of those vaccines in the prevention of infectious diseases. The underlying mechanisms of mRNA vaccines is also discussed, including the double-edged sword of the innate immune response. Finally, the challenges but also the potential of mRNA vaccines are considered.